Hardener-free joint sealant

JP7638908B2Active Publication Date: 2025-03-04HENKEL KGAA
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021571290
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-05-31
Filing Date
2020-05-29
Publication Date
2025-03-04
Estimated Expiration
2040-05-29

Smart Images

  • Figure 0007638908000001
    Figure 0007638908000001
  • Figure 0007638908000002
    Figure 0007638908000002
  • Figure 0007638908000003
    Figure 0007638908000003
Patent Text Reader

Abstract

A curing agent-free sealant composition for sealing joints between male and female components, the sealant composition comprising a solid resin component, a solid (meth)acrylate polyurethane component, and an ethoxylated bisphenol A (meth)acrylate component.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sealant composition that does not include a hardener. Of interest are sealant compositions that are useful for sealing joints. The joints to be sealed include joint conduits for fluids or gases. For example, the joints can be pipe joints. The present invention is useful in the plumbing industry. Of particular interest are materials for sealing threaded pipe joints. [Background technology]

[0002] (Brief Description of Related Art) Non-hardening and solvent-based sealing compounds, PTFE tapes, and hemp pastes have been commonly used to prevent gas and liquid leakage from pipe joints exposed to vibration, pressure and temperature changes. These are pastes made from oils and fillers that lubricate and compress into threads to create a seal, but do not provide a lock. Additionally, they can be squeezed out under pressure, have poor solvent resistance, and do not work on parallel threads.

[0003] Solvent-based sealing compounds also lubricate and compress into the threads, creating a seal, but require the fitting to be re-torqued to minimize voids. Their biggest drawback is that they shrink during curing as the solvent evaporates, compromising the efficiency of the seal.

[0004] PTFE tape provides a good initial seal and resists chemical attack. One advantage is that it acts as a lubricant, but this behavior can cause connections to work loose under dynamic loads, resulting in loss of clamping force and leakage. It can also cause fasteners to be overtightened, stressed, and parts to break. A lot of experience with PTFE tape is required to ensure consistent results, especially when connections must be tightened to a specific position or torque.

[0005] Hemp and paste has been used for many years, but it is tedious and time-consuming to assemble and requires some experience and skill to achieve a complete seal. Another drawback of this sealing method is that it cannot be used for bonds that carry potable water.

[0006] Despite the variety of products that have been produced in the past, the need for alternatives still exists. Summary of the Invention [Means for solving the problem]

[0007] In one aspect, the present invention provides a curing agent-free sealant composition for sealing joints between male and female components, the sealant composition comprising: (a) solid resin component, (b) a solid (meth)acrylate polyurethane component; (c) Contains an ethoxylated bisphenol A (meth)acrylate component.

[0008] The mating part may be, for example, an inter-threaded part where one part (screw) is threaded into another part for engagement between the parts. The parts may be any mating part, but of particular interest in the present invention is a threaded pipe joint where a first (e.g., male) part is threaded into a second (e.g., female) part. When the parts are mated, the composition does not harden (e.g., is uncured for at least 72 hours at room temperature and remains uncured after 72 hours at room temperature) because the composition does not include a curing agent. When the parts are mated, the composition forms a seal (without curing) between the mated parts. Beneficially, the composition forms a seal without the need for curing.

[0009] The hardener-free sealant composition does not include (and does not have) a cure-inducing (cure initiator) component that initiates cure, such as anaerobic cure. For example, the composition does not include (and does not have) toluidines, such as N,N-diethyl-p-toluidine ("DE-pT") and N,N-dimethyl-o-toluidine ("DM-oT"), and acetylphenylhydrazines ("APH"), including maleic acid. For examples of such components, see, for example, U.S. Patent Nos. 3,218,305 (Krieble), 4,180,640 (Melody), 4,287,330 (Rich), and 4,321,349 (Rich). The hardener-free composition of the present invention does not include toluidines, such as N,N-diethyl-p-toluidine ("DE-pT") and N,N-dimethyl-o-toluidine ("DM-oT"), and acetylphenylhydrazines ("APH"), including maleic acid.

[0010] A hardener-free sealant composition does not contain a cure accelerator. Saccharin and APH are used as standard accelerator components in anaerobic adhesive curing systems. In fact, many of the LOCTITE® brand anaerobic adhesive products currently available from Henkel Corporation use only saccharin or both saccharin and APH. A hardener-free composition of the present invention does not contain saccharin and / or APH.

[0011] The composition essentially comprises: (a) solid resin component, (b) a solid (meth)acrylate polyurethane component; (c) It may be composed of an ethoxylated bisphenol A (meth)acrylate component.

[0012] The hardener-free sealant composition of the present invention may be dry to the touch.

[0013] The compositions of the present invention include a solid resin component that may have a melting temperature range of about 55°C to about 80°C and a resolidification temperature range of 25°C to 55°C, as measured by differential scanning calorimetry according to ISO11357-1:2016. Advantageously, the solid resin component having this melting temperature range and resolidification temperature range forms a composition that forms a seal without the need for curing. For example, a joint sealed with a composition including a solid resin component having a melting temperature range of about 55°C to about 80°C and a resolidification temperature range of 25°C to 55°C, as measured by differential scanning calorimetry according to ISO11357-1:2016, remains sealed when exposed to an internal pressure of 0.8 MPa for 5 minutes, as measured according to British Standard BS EN751-2.

[0014] The composition of the present invention includes a solid resin component that may have a melting temperature range of about 55°C to about 80°C and a resolidification temperature range of 25°C to 55°C, as measured by differential scanning calorimetry based on ISO11357-1:2016. For example, the solid resin component may have a melting temperature range of 57°C to 67°C and a resolidification temperature range of 26°C to 38°C, as measured by differential scanning calorimetry based on ISO11357-1:2016. For example, the solid resin component may have a melting temperature range of 56°C to 66°C and a resolidification temperature range of 25°C to 36°C. For example, the solid resin component may have a melting temperature range of 70°C to 80°C and a resolidification temperature range of 45°C to 55°C. For example, the solid resin component may have a melting temperature range of 70°C to 80°C and a resolidification temperature range of 36°C to 49°C.

[0015] In the composition of the present invention, the solid resin component can have a molecular weight of about 2000 g / mol or more, for example, the solid resin component is a copolyester resin having a molecular weight of about 2000 g / mol or more, or a (meth)acrylated polyurethane resin having a molecular weight of about 2,000 g / mol, or a combination thereof. For example, the solid resin component may have a molecular weight in the range of 2,500 to 40,000 g / mol.The solid resin component may have a melt viscosity of about 0.5 to about 20 Pa.s, as measured using an Anton Paar Rheometer Modular Compact Rheometer at a shear rate of 1 inverse second at 80°C.

[0016] In the compositions of the present invention, the solid resin component may be a polyol, such as a polyester polyol.

[0017] In the composition of the present invention, the solid resin component may be a crystalline polyol. Suitably, the solid resin component is not amorphous.

[0018] The compositions of the present invention may have a melting point of about 15°C to about 100°C, such as a melting point of about 30°C to about 100°C, such as a melting point of about 40°C to about 100°C, such as a melting point of about 50°C to about 100°C. Such temperatures compare favorably with those utilized to dry liquid-based formulations. The melting point may be determined by differential scanning calorimetry according to ISO11357-1:2016.

[0019] In the compositions of the present invention, the solid (meth)acrylate polyurethane component may have a melting point in the range of about 30° C. to about 100° C. The melting point may be determined by differential scanning calorimetry according to ISO 11357-1:2016.

[0020] The compositions of the present invention may have a re-solidification point (after melting) in the range of about 10°C to about 50°C, e.g., about 20°C to about 50°C, e.g., about 30°C to about 50°C. Having a re-solidification point in this range usually means that the material will re-solidify when the temperature of the ambient conditions is below 30°C. Thus, the composition will re-solidify under normal ambient conditions. It is understood that re-solidification may not occur at a single temperature, but instead over a range of temperatures. In any case, for purposes of the present invention, the end temperature of re-solidification is desirably 10°C or higher. That is, when exposed to a temperature below the re-solidification point temperature, the composition will return to its solid form. The re-solidification point or range can be determined by differential scanning calorimetry according to ISO11357-1:2016.

[0021] In the composition of the present invention, the solid resin component may be present in an amount of about 10 to about 60% by weight, based on the total weight of the composition, for example, about 25 to about 50% by weight, for example, about 30 to about 40% by weight, based on the total weight of the composition.

[0022] In the compositions of the present invention, the solid (meth)acrylate polyurethane component may be present in an amount of about 10% to about 45% by weight, based on the total weight of the composition.

[0023] In the compositions of the present invention, the solid (meth)acrylate polyurethane component may have a molecular weight of about 1,000 g / mole or less.

[0024] In the compositions of the present invention, the solid (meth)acrylate polyurethane component can have a molecular weight of from about 100 g / mol to about 500 g / mol, for example, from about 200 g / mol to about 300 g / mol.

[0025] For example, the solid (meth)acrylate may include a diisocyanate capped with hydroxyethyl methacrylate such as: [ka] HEMA-IPDI-HEMA with a melting point of about 72-74°C, or

[0026] [ka] HEMA-hMDI-HEMA with a melting point of about 75-85°C, or

[0027] [ka] HEMA-6HXDI-HEMA with a melting point of approximately 75-85°C (this material is referred to as "RRT600" in the example below), or

[0028] [ka] Glycerol dimethacrylate-6HXDI-glycerol dimethacrylate (this material is "4RRT600" in the examples below) having a melting point in the range of about 75 to about 85°C.

[0029] In the compositions of the present invention, the ethoxylated bisphenol A (meth)acrylate component may be present in an amount of about 10% to about 40% by weight, based on the total weight of the composition.

[0030] For example, the composition may include bisphenol A dimethacrylate: [ka] A melting point of approximately 72-74°C, or

[0031] Diethoxylated Bisphenol A Dimethacrylate; [ka] Alternatively, the degree of ethoxylation can be further varied. [ka] In the formula, n+m=2 to 30.

[0032] The composition of the present invention contains less than 1% by weight of solvent based on the total weight of the composition, and may be solvent-free, where the solvent is, for example, an organic solvent or water. One advantage is that the composition of the present invention can be made and / or applied to a substrate in a manner that does not require the use of a solvent, such as an organic solvent or water. This avoids the need for a liquid carrier for the composition. Thus, the hardener-free sealant material of the present invention is essentially dry to the touch, with the resulting handling advantages. For example, the composition for use in the present invention flows when molten or in particulate form, does not require a liquid carrier, and does not require the drying of a solvent or water to achieve application to a mating part.

[0033] Thus, dry processing of the sealant composition, for example on a production line, is achievable and advantageous. Once applied, the compositions of the present invention will also be dry to the touch. A dry to the touch product is desirable from a handling standpoint to eliminate contamination, smudging, spills, loss of composition from the substrate, etc.

[0034] The sealant compositions of the present invention, even when applied to a part, are suitable for storage or handling, such as during shipping, which does not adversely affect the integrity of the applied composition.

[0035] A further advantage of the compositions of the present invention is that there is no cross-contamination when the sealant composition of the present invention comes into contact with another article.

[0036] The compositions of the present invention can be provided in a solid form. In this respect, solid means non-flowable at ambient temperature and having a melting point above about 30° C. Thus, solid does not mean gel.

[0037] In the context of the present invention, tack-free means that the composition has a Shore A hardness of greater than 5. Compositions with a Shore A hardness of less than 5 are not suitable as the compositions are too tacky for dry handling.

[0038] In one aspect, the present invention provides a method for producing a method for treating a cancer cell comprising: (a) providing a composition according to the present invention; (b) applying the composition to at least one mating portion by melting; and (c) subsequently, and optionally after active or passive cooling, providing a method of sealing the joint between the male and female mating portions by bringing the mating portions together to form a joint between the male and female mating portions, and the joint between the male and female mating portions being sealed.

[0039] The mating part may be, for example, an inter-threaded part where one part (the screw) is screwed into another part for engagement between the parts.

[0040] The method of the present invention may include the step of heating the mating portions of the articles to be sealed to a temperature sufficient to melt the composition.

[0041] It is understood by those skilled in the art that in order to apply the composition for use in the present invention, sufficient melting can be performed to allow the composition to be applied to the mating part in a manner that allows it to adhere. By melting the composition for application, the need for a liquid carrier for the composition is avoided. The expression tack-free and dry to the touch refers to the composition after it has been (melted) applied to the mating part and then (re)solidified. Testing to confirm that the mating part is dry to the touch should only be performed after the composition is no longer in molten form. For example, testing should be performed at least about 30 minutes after the composition has been applied.

[0042] In accordance with the method of the present invention, preferably at least one of the female mating portion or the male mating portion, or both mating portions, are formed from a metal, such as steel, copper, or brass.

[0043] A system is provided that includes a sealed joint, where the joint is sealed by the method of the present invention.

[0044] In the system of the present invention, the sealed joint allows the passage of fluid or gas through the male and female mating portions and, advantageously, the joint remains sealed when placed under pressure from the fluid or gas.

[0045] In one aspect, the present invention provides a sealed joint comprising a male mating portion and a female mating portion and a composition of the present invention.

[0046] A sealed joint according to the present invention may be one in which the male or female mating portions, or both, are formed from a metal, such as steel, copper, or brass.

[0047] A sealed joint according to the present invention may be one in which the joint remains sealed when subjected to an internal pressure of 0.8 MPA for 5 minutes, measured in accordance with British Standard BS EN751-2.

[0048] A sealed joint according to the present invention may be one in which the joint remains sealed when exposed to an internal pressure of 0.8 MPa for 5 minutes after the fitting is returned, as measured in accordance with British Standard BS EN751-2.

[0049] Surprisingly, it has been found that such sealant compositions are capable of sealing joints, such as pipe joints, and maintaining a seal even after the pipe is retracted. Advantageously, the sealant compositions of the present invention do not include a hardener and do not harden. Retracting the pipe allows modifications to be made to the joints when installing the pipe system. The joints formed from the fittings can be adjusted and one fitting can be rotated while maintaining the seal formed by the composition of the present invention. The hardenable composition becomes brittle and breaks when retracted.

[0050] A sealed joint according to the present invention may be one in which the bond remains sealed when exposed to an internal pressure of 0.8 MPa for 5 minutes after the mating parts have been put back together after 72 hours, as measured in accordance with British Standard BS EN751-2.

[0051] A sealed joint according to the present invention may be one in which the joint remains sealed when the sealed joint is exposed to a temperature of 130°C for 168 hours followed by an internal pressure of 0.8 MPa for 5 minutes, as measured in accordance with British Standard BS EN751-2.

[0052] The sealed joint according to the invention has a mechanical strength measured in accordance with British Standard BS EN751-2 of: (a) Heat the sealed joint to 100°C for 22 hours and cool to 20°C for 2 hours; (b) repeating step (a) five times; (c) The sealed joint was then cooled to -20°C for 4 hours. (d) heating the sealed joint to 20°C for 2 hours; After being temperature cycled, the joint remains sealed when exposed to an internal pressure of 0.8 MPa for 5 minutes.

[0053] Surprisingly, it has been found that such sealant compositions can easily seal joints, such as pipe joints, and can withstand temperature cycling while maintaining a seal. Compositions that do harden tend to be brittle and brittle and therefore do not maintain a seal when exposed to thermal cycling. The hardener-free compositions of the present invention maintain a seal when exposed to thermal cycling.

[0054] In one embodiment, the use of the composition of the present invention is for use to seal a joint between male and female mating parts. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0055] (Detailed Description) A hardener-free sealant composition for sealing joints according to the present invention was prepared as described in the experimental section below.

[0056] (experiment) Examples of compositions that can be considered as a basis for formulating (100%) hardener-free sealant compositions are shown in Table 1 below.

[0057] [Table 1]

[0058] An important prerequisite for the resins and solid (meth)acrylates used is that they are generally solid at room temperature and have a melting point below 100°C.

[0059] (preparation) The raw materials are blended together at a temperature just above the melting point of the individual components. Once the blend is homogeneous in appearance, it is allowed to cool to room temperature. At this point it is a solid. EXAMPLES

[0060] The following composition was prepared in which the solid resin was Dynacoll 7380 and the solid (meth)acrylate was 2-methacryloxyethyl phenyl urethane.

[0061] [Table 2]

[0062] (Shore A hardness test) Test samples 1, 3-5 and the comparative test specimen were tested for Shore A hardness using a durometer. The test samples achieved a Shore A hardness of greater than 5. The comparative sample was too soft to measure.

[0063] (Joint sealing) The sealant composition was heated until melted and applied to the male pipe. The coated pipe was allowed to sit overnight before assembling the male and female pipes.

[0064] (Test 1: Internal pressure test after assembly) The specimens were tested 30-60 minutes after assembly in accordance with the test method of BS EN751-2. The pipes were immersed in a water bath at approximately 23°C. The specimens were pressurized using compressed air at a pressure of 8 bar (0.8 MPa) ± 1 bar (0.1 MPa). Gas leakage was determined by the appearance of air bubbles during the 5 minute immersion period, ignoring any bubbles recorded during the first 15 seconds of immersion.

[0065] (Test 2: Undo test) The test assembly was turned back at 45°. After 10 minutes and 72 hours of turning back, the internal pressure test for leaks was repeated using compressed air.

[0066] (Test 3: Hot water resistance test) The test assembly was half filled with tap water and closed with a plug seal. The assembly was placed in a horizontal position in an oven at 130°C for 168 hours. After this period, the assembly was cooled to room temperature for 2 hours, the plug was removed and the water was drained. The internal pressure test for leaks was repeated with compressed air.

[0067] (Test 4: Temperature cycle test) The test assembly was placed in a temperature chamber at 150°C for 22 hours and then cooled to 20°C for 2 hours. The temperature cycle test was repeated many times. The specimens were then cooled to -20°C for 4 hours and warmed to 20°C for 2 hours. The internal pressure test for leakage was repeated with compressed air.

[0068] The following composition was prepared in which the solid resin was a urethane methacrylate endcapped crystalline polyol and the solid (meth)acrylate was 2-methacryloxyethyl phenyl urethane. [Table 3]

[0069] Comparative Example 3 The following compositions were prepared that contained a curable component (Loctite 577 with anaerobic cure system): [Table 4]

[0070] The results are as follows: [Table 5]

[0071] (Differential Scanning Calorimetry (DSC)) Differential scanning calorimetry (DSC) can indicate the physical properties of functionalized resins by determining the heat flux response to changes in thermal conditions. Samples were analyzed using a Perkin Elmer DSC6000. The sample to be analyzed was placed in an aluminum pan in an amount of 10-15 mg and placed in a sample holder in a furnace. The sample was heated from -30°C to 100°C at a rate of 10°C per minute and then cooled to -20°C at a rate of 10°C / min to measure the melting and resolidification temperature ranges in accordance with ISO11357-1:2016. Samples were prepared as described above. Samples were prepared as follows: [Table 6]

[0072] The crystalline polyols of Examples 7-12 and Comparative Examples 4-8 were tested to determine the melting and resolidification temperature ranges in accordance with ISO 11357-1:2016. Where possible, compositions were formulated and tested to determine the melting and resolidification temperature ranges in accordance with ISO 11357-1:2016, and internal pressure tests were performed after assembly. The results are shown below.

[0073] [Table 7]

[0074] The crystalline polyester polyols of Examples 7 to 10 have a melting temperature range of 55° C. to 80° C. and a resolidification temperature range of 25° C. to 55° C. Compositions prepared using these crystalline polyester polyols pass the internal pressure test.

[0075] The amorphous and semi-crystalline polyester polyols of Comparative Examples 4-7 do not have both a melting temperature range of 55°C to 80°C and a resolidification temperature range of 25°C to 55°C. For example, Comparative Examples 4 and 5, which have a melting temperature range of 55°C to 80°C, do not resolidify. These amorphous or semi-crystalline polyols did not mix with other ingredients to form a composition. In Comparative Example 6, the semi-crystalline polyol did not resolidify, but it was possible to formulate a composition, but the composition did not pass the internal pressure test.

[0076] The blend of crystalline polyols has a melting temperature range of 55°C to 80°C and a resolidification temperature range of 25°C to 55°C and can be blended with polyols that may not have a resolidification temperature range to form compositions that pass the instant seal test versus Comparative Example 8. Blends of polyols that do not have a resolidification temperature range will not form compositions that pass the instant seal test.

[0077] The words "comprises / comprising" and "having / including" when used herein in relation to the present invention are used to specify the presence of stated features, integers, steps or ingredients, but do not exclude the presence or addition of one or other features, integers, steps, ingredients, or groups thereof.

[0078] It will be appreciated that certain features of the invention that are, for clarity, described in the context of separate embodiments, can also be provided in combination in a single embodiment. Conversely, various features of the invention that are, for brevity, described in the context of a single embodiment, can also be provided separately or in any suitable subcombination.

Claims

1. 1. A toluidine, acetylphenylhydrazine and saccharin-free sealant composition for sealing joints between male and female components, the sealant composition comprising: (a) solid resin component, (b) a solid (meth)acrylate polyurethane component; (c) a sealant composition comprising an ethoxylated bisphenol A (meth)acrylate component, the solid resin component is a polyester polyol; the solid resin component has a melting temperature range of 55° C. to 80° C. and a resolidification temperature range of 25° C. to 55° C., as measured by differential scanning calorimetry in accordance with ISO 11357-1:2016; The solid resin component is present at 30% to 45% by weight based on the total weight of the composition; the solid (meth)acrylate polyurethane component is present in an amount of 30% to 45% by weight; A composition wherein the ethoxylated bisphenol A (meth)acrylate component is present in an amount of from 10% to 40% by weight.

2. The composition comprises: (a) solid resin component, (b) a solid (meth)acrylate polyurethane component; The composition of claim 1 comprising the component (c) ethoxylated bisphenol A (meth)acrylate.

3. The composition of claim 1 or 2, wherein the solid resin component has a molecular weight of 2,000 g / mol or more.

4. A composition described in any one of claims 1 to 3, wherein the solid resin component is a copolyester resin having a molecular weight of 2,000 g / mol or more, or a (meth)acrylated polyurethane resin having a molecular weight of 2,000 g / mol, or a combination thereof.

5. The composition according to any one of claims 1 to 4, wherein the composition has a melting point of from 15°C to 100°C.

6. The composition of claim 5, wherein the composition has a melting point of 30°C to 100°C.

7. The composition of claim 6, wherein the composition has a melting point of 40°C to 100°C.

8. The composition of claim 7, wherein the composition has a melting point of 50°C to 100°C.

9. The composition of any one of claims 1 to 8, wherein the solid (meth)acrylate polyurethane component has a melting point in the range of from 30°C to 100°C.

10. The composition of any one of claims 1 to 9, wherein the composition has a refreezing point in the range of from 10°C to 50°C.

11. The composition of any one of claims 1 to 10, wherein the solid resin component is present in an amount of 30 to 40% by weight, based on the total weight of the composition.

12. The composition of any one of claims 1 to 11, wherein the solid (meth)acrylate polyurethane component has a molecular weight of 1,000 g / mole or less.

13. The composition of claim 12, wherein the solid (meth)acrylate polyurethane component has a molecular weight of from 200 g / mole to 500 g / mole.

14. The composition of claim 13, wherein the solid (meth)acrylate polyurethane component has a molecular weight of 200 g / mole to 300 g / mole.

15. The composition of any one of claims 1 to 14, wherein the composition does not contain less than 1% by weight of an organic solvent or water solvent, based on the total weight of the composition.

16. The composition according to any one of claims 1 to 15, wherein the composition is provided in a solid form.

17. (a) providing a composition according to claims 1 to 16, (b) applying the composition to at least one mating portion by melting; (c) subsequently sealing the joint between the male and female mating portions by joining the mating portions to form a joint between the male and female mating portions and sealing the joint between the male and female mating portions.

18. The method of claim 17, wherein in step (c), after active or passive cooling, the mating portions are joined to form a joint between the male and female mating portions, and the joint between the male and female mating portions is sealed.

19. 19. The method of claim 17 or 18, comprising the step of heating the mating portions of the articles to be sealed to a temperature sufficient to melt the composition.

20. The method of any one of claims 17 to 19, wherein at least one of the female mating portion or the male mating portion, or both mating portions, are formed from metal.

21. The method of claim 20, wherein the metal is steel, copper, or brass.

22. A system comprising a sealed joint, wherein the joint is sealed by the method of claims 17-21.

23. The system described in claim 22, wherein the sealed joint allows the passage of fluid or gas through the male and female mating portions.

24. A sealed joint having a male mating portion and a female mating portion and a composition according to any one of claims 1 to 16.

25. 25. The sealed joint of claim 24, wherein the male mating portion or the female mating portion, or both mating portions, are formed from metal.

26. The sealed joint of claim 25, wherein the metal is steel, copper, or brass.

27. 27. A sealed joint according to any one of claims 24 to 26, wherein the joint remains sealed when subjected to an internal pressure of 0.8 MPA for 5 minutes, measured in accordance with British Standard BS EN751-2.

28. 28. A sealed joint according to any one of claims 24 to 27, wherein the joint remains sealed when exposed to an internal pressure of 0.8 MPa for 5 minutes after the fittings have been undoped, measured in accordance with British Standard BS EN751-2.

29. A sealed joint as described in claim 28, which remains sealed when exposed to an internal pressure of 0.8 MPa for 5 minutes after the fitting is returned for a maximum of 72 hours, as measured in accordance with British Standard BS EN 751-2.

30. 27. A sealed joint according to any one of claims 24 to 26, wherein the joint remains sealed when exposed to an internal pressure of 0.8 MPa for 5 minutes after the sealed joint has been exposed to a temperature of 130°C for 168 hours, as measured in accordance with British Standard BS EN751-2.

31. The sealed joints were measured according to British Standard BS EN 751-2 to (a) heating the sealed joint to 100°C for 22 hours and cooling to 20°C for 2 hours; (b) repeating (a) five times; (c) The sealed joint is then cooled to −20° C. for 4 hours; (d) heating the sealed joint to 20° C. for 2 hours; 27. The sealed joint of any one of claims 24 to 26, wherein after being temperature cycled, the joint remains sealed when exposed to an internal pressure of 0.8 MPa for 5 minutes.

32. Use of a composition according to any one of claims 1 to 16 for sealing a joint between male and female mating parts.

Citation Information

Patent Citations

  • Low-cost anaerobic adhesive and preparation method thereof

    CN105176422A

  • Sealer tape or sheet or formed product therefrom

    JP1989110585A

  • Liquid crystal sealant and liquid crystal cell using the same

    JP2016024240A

  • Liquid crystal sealant and liquid crystal cell using the same

    JP2016024243A

  • Anaerobic hardening components

    JP2019500438A